COMMUNITY INVOLVEMENT IN CRISIS MANAGEMENT: A CASE STUDY OF MACAO ‘s PANDEMIC MANAGEMENT DURING THE COVID-19 - Ng Pui Weng (University of Saint Joseph, 2024)
The aim of this study is to analyze the crisis management of Macao SAR and the extent to which the community were engaged in the COVID-19 pandemic prevention and control. There are some issues found that when the pandemic breaks out and after outbreaks, such as poor information communication, low efficiency of prevention and control work, unsatisfactory compliance of the public, lack of pandemic prevention materials which affect the government's control of the pandemic in the past study. In Macao SAR, densely residential areas and dense population are the main considerations for pandemic prevention and control. Communities, as the main first line of defense for pandemic prevention and control, are also the bridge for communication between the government and the residents. The community have the advantages of timely and accurate information collection and accurate implementation of prevention and control measures. In this study found that the involvement of the Macao community may not be the key to the success of epidemic prevention in Macao. Community participation also faces many challenges, such as uneven distribution of facilities and services, lack of medical expertise of community workers, shortage of manpower and other shortcomings of community participation. It is possible that the Macao community is not playing a key role in the COVID-19 pandemic prevention and control. Given this scenario, the government needs to give full play to social forces and the role of the community in pandemic prevention and control. Currently, there are few studies on community involvement in COVID-19 prevention and control. Through COVID-19, this study puts forward some ideas that the government needs to pay attention to community development and improve citizens' community awareness to promote the Macao community. Improving the Macao community is conducive to Macao in the future crisis and community cooperation
Keywords: Digital Finance; Digital Financial Infrastructure; Greater Bay Area; Thesis and Dissertations Master of Community Development (MCD); University of Saint Joseph

NEUROCINEMATIC: WALTER MURCH’S VIDEO EDITING PROCESS AND FILM SOUND DESIGN CASE STUDY - Nyögéri, José (University of Saint Joseph, 2024)
This dissertation examines the enduring influence of Walter Murch's seminal editing principles and techniques on contemporary film editors, highlighting how his ideas continue to shape the craft even among those who may not be directly aware of his work. Central to this study is an exploration of Murch's ""Rule of Six,"" which prioritizes emotion, story, rhythm, eye-trace, two-dimensional plane of the screen, and three-dimensional space of action in editing decisions. Additionally, the research delves into Murch's concepts of rhythm and pacing, as well as his emphasis on preserving the emotional impact of a scene. Through a series of in-depth interviews with working editors, this dissertation investigates the extent to which Murch's theoretical framework is manifested in modern editing practices. The study seeks to identify how contemporary editors incorporate these principles into their workflows, consciously or subconsciously, and how these techniques contribute to the narrative and emotional effectiveness of their films. By analyzing the practical decision-making processes of today's editors, this research aims to uncover the degree to which Murch's legacy endures in the film industry. The findings underscore the significant, yet often implicit, role that Murch's editing philosophy plays in shaping the aesthetic and emotional resonance of contemporary cinema. This dissertation thus provides a comprehensive understanding of the lasting impact of Walter Murch's contributions to the art and science of film editing
Keywords: Neurocinematic; Sound Design; Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph; Video Editing; Walter Murch